2012
DOI: 10.4172/2155-9546.1000137
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth and Survival of Juvenile Atlantic Cod (Gadus morhua)Cultured in Copper and Nylon Net Pens

Abstract: Bio-fouling on net pens has been a major concern for the marine aquaculture industry. As cage systems increase in size, so does the surface area for the attachment of colonial organisms that create drag on the net, reduce water flow important to fish health, and increase operational expenses due to net cleaning. To solve this problem, the International Copper Association (ICA) has been developing copper alloy netting for sea cages. Copper netting has unique properties that minimize bio-fouling, reduce the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The higher mechanical strength of the copper alloy fish net pens prevents the loss of fish through escapes (Dwyer and Stillman, 2009;Drach, 2013). Also Chambers et al (2012) reported that the strength of copper netting also deters predators such as seals and sharks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher mechanical strength of the copper alloy fish net pens prevents the loss of fish through escapes (Dwyer and Stillman, 2009;Drach, 2013). Also Chambers et al (2012) reported that the strength of copper netting also deters predators such as seals and sharks.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the mechanical, economic or environmental advantages of copper alloy mesh compared to the traditional nylon nettings (Chambers et al, 2012;Aufrecht et al, 2013;Drach, 2013;González et al, 2013;Ayer et al, 2016;Efstathiou et al, 2016;Kalantzi et al, 2016;Yigit et al, 2016;Buyukates et al, 2017;Yigit et al, 2017Yigit et al, , 2018, and the higher structural stability of the copper alloy nets exposed to high energy water conditions assuring volumetric integrity in the cage environment and preventing deformation on the structure (Berillis et al, 2017), the construction and assembly of the new technology mesh pens and moreover forming the material into a fish cage is a new challange still remaining as a question to be answered and an issue that might interest fish cage producers and net manufacturers. Moving cage aquaculture to more exposed sites has brought cage farmers to re-consider materials and equipment for cost effective production with higher economic benefits and production of healthier fish.…”
Section: Introductionmentioning
confidence: 99%
“…The fish net pens made of copper alloy appear to have comparative mechanical, economic and environmental advantages over the conventional polymer ones (Chambers et al, 2012;Aufrecht et al, 2013;Drach, 2013;González et al, 2013;Ayer et al, 2016;Efstathiou et al, 2016;Kalantzi et al, 2016;Yigit et al, 2016;Buyukates et al, 2017). Copper alloy fish nets have higher structural stability.…”
mentioning
confidence: 99%
“…When copper alloy fish nets are introduced into seawater they develop an adherent protective patina layer. That layer inhibits corrosion and resists the attachment of fouling organisms (Chambers et al, 2012;Aufrecht et al, 2013;Drach, 2013). A clean net maintains water movement through the cage for optimal fish health.…”
mentioning
confidence: 99%
See 1 more Smart Citation